Combining children's savings account programs with scholarship programs: Effects on math and reading scores. (July 2019) - Elliott, William; Chowa, Gina; Ellis, James; Chen, Zibei; O'Brien, Megan
Abstract: The study examines school data and their association with participation in the Wabash County Promise Scholarships program, which combines Children's Savings Accounts (CSAs) with scholarships. CSAs are interventions designed to build educational assets for school age children. Policy makers are increasingly turning to CSAs as a way to augment efforts for improving children's educational outcomes. Findings from this study provide some evidence that having a CSA combined with a scholarship is associated with higher math and reading scores. Findings are strongest among the subsample receiving free/reduced lunch. Further, findings suggest that being a saver (i.e., having at least one family or champion contribution) in Promise Scholars is associated with higher math scores but not reading scores. Finally, evidence suggests that CSAs combined with scholarships in the Promise Scholars program are more closely associated with children's math and reading scores than only CSAs. Highlights: The study examines the combination of Children's Savings Accounts (CSAs) and scholarships. Having a CSA combined with a scholarship is associated with higher math and reading scores. Findings are strongest among the subsample receiving free/reduced lunch. Being a saver is associated with higher math scores but not reading scores. CSAs with scholarships are more closely associated with children's scores than only CSAs.